2019
DOI: 10.1155/2019/7024905
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory Effects of Subcutaneous Immunotherapy on Lymphocyte Subgroups and Cytokines in Children with Asthma

Abstract: Objective Asthma is a syndrome that incorporates many immune phenotypes. The immunologic effects of subcutaneous immunotherapy (SCIT) exerts on allergic asthma remain still largely unknown. Here, we investigated the effects of SCIT on cytokine production and peripheral blood levels of lymphocyte subtypes in children with mite-induced moderate and severe allergic asthma. Methods The study included 60 kids with mite-induced allergic asthma from 5 to 10 years old. All subjects had received antiasthmatic pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…134 In patients with asthma, blood ILC2 frequency and IL-13 levels were reduced with SCIT and pharmacotherapy compared with pharmacotherapy alone. 135 Significant decreases in circulating ILC2 numbers were observed in newly diagnosed patients with asthma after budesonide treatment. 113 Budesonide also inhibited phosphorylation of signal transducer and activator of transcription proteins and JAK3 and greatly reduced type 2 cytokine production from ILC2s in vitro.…”
Section: Ilcs In Allergic Diseases Asthmamentioning
confidence: 97%
“…134 In patients with asthma, blood ILC2 frequency and IL-13 levels were reduced with SCIT and pharmacotherapy compared with pharmacotherapy alone. 135 Significant decreases in circulating ILC2 numbers were observed in newly diagnosed patients with asthma after budesonide treatment. 113 Budesonide also inhibited phosphorylation of signal transducer and activator of transcription proteins and JAK3 and greatly reduced type 2 cytokine production from ILC2s in vitro.…”
Section: Ilcs In Allergic Diseases Asthmamentioning
confidence: 97%
“…Genetic and immunological evidence indicates that Treg cells play pivotal roles in promoting tolerance to allergens and preventing allergic asthma [139]. Moreover, a number of studies have investigated associations of impaired function and decreased frequencies of Treg cells with the development of allergic asthma [140][141][142]. Adoptive transfer of antigenspecific Treg cells suppressed allergic inflammation and airway hyperreactivity in asthmatic mice [143].…”
Section: The Role Of Anti-inflammatory Treg Cells In Asthmamentioning
confidence: 99%
“…These studies emphasized that the reconstitution of antigen-specific FOXP3 + Tregs was found to subdue allergic inflammatory responses and hyper reactivity via the IL-10 dependent pathway [33,81,101], and further downregulated established inflammation and prevent airway remodeling when injected after disease onset [102]. The therapeutic application of Tregs has been tested in clinical and preclinical platforms to achieve desired immunosuppression and to suppress asthma inflammation [89,[102][103][104][105][106][107].…”
Section: Regulatory T Cellsmentioning
confidence: 99%